2018
DOI: 10.1007/s10549-018-4839-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of long non-coding RNA MALAT1 in breast cancer is associated with poor relapse-free survival

Abstract: High expression of lncRNA MALAT1 is associated with breast cancer relapse and may play a role in tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…In human breast cancer tissues, MALAT1 has been reported to be aberrantly up-regulated and high levels of MALAT1 expression correlate with poor patient prognosis (Chou et al, 2016;Feng et al, 2016;Wang et al, 2018). MALAT1 binds miR-1, miR-124, and miR-448, and acts as a ceRNA to reduce CDC42 and up-regulate CDK4 expression, leading to breast cancer cell cycle progression, cell migration, and invasion (Chou et al, 2016;Feng et al, 2016;Bamodu et al, 2016).…”
Section: The Controversy: Oncogenic and Tumor Suppressive Functions Omentioning
confidence: 99%
“…In human breast cancer tissues, MALAT1 has been reported to be aberrantly up-regulated and high levels of MALAT1 expression correlate with poor patient prognosis (Chou et al, 2016;Feng et al, 2016;Wang et al, 2018). MALAT1 binds miR-1, miR-124, and miR-448, and acts as a ceRNA to reduce CDC42 and up-regulate CDK4 expression, leading to breast cancer cell cycle progression, cell migration, and invasion (Chou et al, 2016;Feng et al, 2016;Bamodu et al, 2016).…”
Section: The Controversy: Oncogenic and Tumor Suppressive Functions Omentioning
confidence: 99%
“…A previous meta-analysis has shown that the up-regulation of MALAT-1 is significantly correlated with the prognosis and metastasis of cancers [17]. Nevertheless, the prognostic role of MALAT-1 in breast cancer is poorly characterized, with no systematic evaluation conducted to date [18,19]. Therefore, we conducted a systematic review to investigate the associations of MALAT-1 with clinicopathological features and survival of patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1a, b). Importantly, one of the identified TROLLs was MALAT1, previously demonstrated to promote different metastatic tumour types in humans [15][16][17] , including breast cancer where high levels of this lncRNA correlate with higher risk of relapse and reduced overall survival [18][19][20] . We performed qRT-PCR and found that 6 TROLLs were upregulated and three were downregulated in TAp63 −/− MECs compared with WT MECs (Fig.…”
Section: Resultsmentioning
confidence: 99%